ELISPOT assay of the SARS-CoV-2 specific T cells immune response - V. V. Gerasimova; S. V. Kolesnik; D. A. Kudlay; A. S. Golderova (Acta Biomedica Scientifica, 2022)
The COVID-19 pandemic has stimulated interest in the development of biotechnology, as well as in the search for new solutions in the diagnostics of immune processes. The response of immunoglobulins A, M and G had a significant role in the assessment of virus-specific immune responses. Later, it was understood that for a comprehensive assessment of adaptive immunity processes, it is reasonable to study its cellular component. One of the most affordable methods for assessing T cell immunity, which has proven itself in the diagnosis of other infectious diseases, such as latent tuberculosis infection, is IGRA ELISPOT.The aim of the study. To determine SARS-СoV-2 specific immune response of T lymphocytes in vitro in the peripheral blood of volunteers from various groups using IGRA ELISPOT method. We evaluated the applicability of the method to assess T cell immune response to infection and vaccination. In addition, we determined the duration of the maintenance period of the SARS-CoV-2 specific T cells immune response induced by vaccination.Materials and methods. The study was carried out on venous blood samples of volunteers from three groups: 1) hospital patients with COVID-19; 2) COVID-19 convalescents; 3) vaccinated against COVID-19. The T cell immune response was assessed using the TigraTest® SARS-CoV-2 test system, which determines in vitro the number of T cells secreting interferon-gamma in response to stimulation with SARS-СoV-2 peptides in two antigens panels: 1) peptides of the spike protein (S); 2) peptides of N, M, Orf3a and Orf7a proteins.Conclusion. The IGRA ELISPOT assay is a specific and sensitive tool in the assessment of T cell immunity to the SARS-CoV-2 virus. The method makes it possible to assess SARS-CoV-2 specific T cell responses induced both by natural encounter with the pathogen and by vaccination. It is advisable to use the method in routine practice for comprehensive assessment of immunity to SARS-CoV-2.